Pengembangan Dtw Museum Perjuangan 10 November 1945 Sebagai Pariwisata Berbasis Sejarah Di Kota Surabaya, Provinsi Jawa Timur - De Prito, Andreas Mardwido; Suryasih, Ida Ayu; Mahagangga, I Gusti Agung Oka; Ariwangsa, I Made Bayu (JURNAL DESTINASI PARIWISATA, 2021)
The Museum of Tenth November Surabaya is the only museum that keeps a history of the struggle of the arek-arek Suroboyo in maintaining the independence of the Republic of Indonesia. To commemorate the services of the warriors, the Heroes Monument was erected. In order to support the Heroes Monument, an underground museum was built so as not to disturb the main attraction, namely the Heroes Monument itself. Nowadays, the people of Surabaya are less aware of the history of the fighters so they are less interested in visiting this museum. This study uses a qualitative method which aims to identify The Museum of Tenth November Surabaya as historical tourism. Data collection in this study were observation, in-depth interviews, and documentaries. Determination of informants is done by purposive sampling. The data analysis used is descriptive qualitative. Observation results show The Museum of Tenth November Surabaya stores 47 collections and 4 weapons of war from allied spoils. Based on the SWOT analysis, the results of this study are the Surabaya Tenth November Museum which has the potential of innovation that can be developed to attract more tourists who come to visit. Keyword: Heroes Monument, The Museum of Tenth November Surabaya, Development of Tourist Attraction, Heritage Tourism, SWOT.